2017
DOI: 10.18203/2394-6040.ijcmph20171757
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of cholera at Dutsen-Abba Ward Zaria local government area, Kaduna State Nigeria 2015: the importance of hygienic practices

Abstract: Background: Cholera is an infection caused by Vibrio cholerae, which may lead to severe dehydration and death if not treated promptly. On August 31, 2015, the Kaduna Ministry of Health received a notification of increase cases of vomiting and diarrhoea at Dusten-Abba in Zaria. A response Team was sent to confirm the outbreak, describe the socio-demographic characteristics and identify possible risk factors for the outbreak.Methods: We defined cases according to the world health organization (WHO) criteria. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In general, the distribution of cholera cases by age and sex in Nigeria is dynamic given the mixed available evidence. For instance, some studies have reported higher number of cholera cases in adults than in children [1116] and vice-versa [17, 18], and some studies have similarly reported higher number of cholera cases in females than in males [4, 12, 19] and vice-versa [20, 21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the distribution of cholera cases by age and sex in Nigeria is dynamic given the mixed available evidence. For instance, some studies have reported higher number of cholera cases in adults than in children [1116] and vice-versa [17, 18], and some studies have similarly reported higher number of cholera cases in females than in males [4, 12, 19] and vice-versa [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a homogenous definition of cholera especially in an endemic setting such as Nigeria made the direct comparison of our findings with similar studies challenging. For example, studies in Nigeria have used 5 years [12, 17, 40], 2 years [21, 41, 42], and no age restrictions [14, 19] for the definition of suspected cholera cases. Thus, this challenge should be prioritised by the GTFCC given the relevance to cholera case management and assessment of cholera burden, which would be strategic in the objective assessment of the global roadmap goals of cholera elimination by 2030.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution pattern of cholera cases by age and sex is largely dynamic in Nigeria, as there are mixed available reports. A study reported higher number of cholera cases in adults than in children [ 16 ], whereas more cholera cases were reported in children than adults by another study [ 17 ]. Furthermore, some studies have reported higher number of cholera cases in females than in males [ 16 ] and vice-versa [ 18 ].…”
mentioning
confidence: 99%
“…A study reported higher number of cholera cases in adults than in children [ 16 ], whereas more cholera cases were reported in children than adults by another study [ 17 ]. Furthermore, some studies have reported higher number of cholera cases in females than in males [ 16 ] and vice-versa [ 18 ]. In conformity with the findings of Nnaji et al [ 18 ], our study showed significant association between the number of cholera cases and the sex of patients.…”
mentioning
confidence: 99%
“…6,31,35,36 Contrarily, studies carried out in Nigeria, Ethiopia, Bangladesh, and Malta revealed that cases of acute watery diarrhoea were observed more among patients in their middle adolescence, early adulthood and older age groups as opposed to younger children. 25,28,[37][38][39][40][41] Additionally, a greater proportion of all line-listed patients were slightly more males than females. This is in agreement with the previous studies done in Nigeria, South Africa, Ethiopia, and India.…”
Section: Discussionmentioning
confidence: 99%